Rectal Clear Cell Carcinoma Arising from Endometriosis: Case Report and Literature Review - Adriana Ioana Gaia-Oltean; Dan Boitor-Borza; Voicu Caius Simedrea; Vlad Braicu; Laura-Ancuta Pop; Romeo Micu (Diagnostics)
Background and Clinical Significance: Endometriosis is a common gynecological disease that can occasionally be associated with malignant transformation. The most common site of malignant transformation is the ovary, but there can also be rare extragonadal endometriosis-associated malignancy sites, such as the intestines, rectovaginal septum, and abdominal wall. A low number of malignant degenerations of rectal endometriosis are described in the literature. However, the majority of these cases report endometrioid adenocarcinoma as the most frequent histopathological type of tumor. On the other hand, Müllerian clear cell carcinoma is sporadic. Case Presentation: We present the case of a 43-year-old woman with clear cell carcinoma of the rectum, which developed on an endometriosis nodule, and the surgical outcome. Imaging of the case was performed by MRI. The patient was offered curative surgery. The pathology report confirmed a clear cell carcinoma developed on an endometriosis lesion, and immunochemistry helped in the characterization of the tumor. The patient developed a rectovaginal fistula. An ileostomy and surgical repair of the fistulous opening were performed, with a favorable postoperative recovery. Conclusions: Malignant transformation of endometriosis lesions is possible and should be taken into consideration. Müllerian clear cell carcinoma development within rectovaginal endometriosis is extremely rare.